Diversification of the Pristimantis conspicillatus group (Anura: Craugastoridae) within distinct neotropical areas throughout the Neogene. Issue 1 (31st December 2022) - Fouquet, Antoine; Réjaud, Alexandre; Rodrigues, Miguel T.; Ron, Santiago R.; Chaparro, Juan C.; Osorno, Mariela; Werneck, Fernanda P.; Hrbek, Tomas; Lima, Albertina P.; Camacho-Badani, Teresa; Jaramillo-Martinez, Andres F.; Chave, Jérôme
Abstract : Determining the relative importance of dispersal and vicariance events across neotropical regions is a major goal in biogeography. These events are thought to be related to important landscape changes, notably the transition of Amazonia toward its modern hydrological configuration ca. 10 million years ago. We investigated the spatio-temporal context of the diversification of one of the major lineages of Pristimantis, a widespread and large genus of direct-developing Neotropical frogs. We gathered a spatially and taxonomically extensive sampling of mitochondrial DNA sequences from 754 Pristimantis gr . conspicillatus specimens, which led to delimiting 75 Operational Taxonomic Units (OTUs). Complete mitogenomes of 35 of these OTUs were assembled and collated with two nuDNA loci to reconstruct a time-calibrated phylogeny. We identified five major clades that diverged around the Oligocene-Miocene transition and that are largely restricted to distinct Neotropical regions i.e. Western Amazonia ( P. conspicillatus clade), the Brazilian Shield ( P. fenestratus clade), the Atlantic Forest ( P. ramagii clade), the Guiana Shield ( P. vilarsi clade) and the northern Andes ( P. nicefori clade). The majority of the diversification events within these clades occurred in-situ from the early Miocene onward. Yet, a few ancient dispersal/vicariance events are inferred to have occurred among trans-Andean forests, the Atlantic Forest, the Brazilian and the Guiana Shields, but almost none in the last 10 Ma. The radical landscape transformations during the Miocene caused by the Andean orogeny and hydrological barriers such as the Pebas System and the subsequent transcontinental configuration of the Amazon drainage is a likely explanation for the isolation of the different clades within the P. gr . conspicillatus .